Eosinophilic granulomatosis with polyangiitis in children: Data from the French RespiRare® cohort. Issue 12 (26th June 2018) - Fina, Agnès; Dubus, Jean‐Christophe; Tran, Antoine; Derelle, Jocelyne; Reix, Philippe; Fayon, Michael; Couderc, Laure; Donnou, Marie‐Dominique; Pagnier, Anne; Blanchon, Sylvain; Faure, Nathalie; Mely, Laurent; et al.
Abstract: Objectives: To describe the characteristics of pediatric cases of eosinophilic granulomatosis with polyangiitis (EGPA), a systemic necrotizing vasculitis rarely diagnosed in children, retrieved from the French Reference Center for rare pediatric lung diseases and compared with adult cases included in the French Vasculitis Study Group cohort. Methods: We collected information on pediatric EGPA disease presentation, management, and outcome. Cases met the Lanham criteria and/or American College of Rheumatology classification criteria. Results: Fourteen cases of pediatric EGPA were included, from 1980 to 2012, with a median follow‐up of 58.5 months. Median age at diagnosis was 12.3 years. All cases had respiratory involvement. The organ systems most frequently involved were the upper airway (85%), skin (71%), digestive tract (64%), and heart (57%). Neurological and renal involvement were rare. Four of the fourteen children were positive for ANCA (30.7%). During follow‐up, three children required intensive care and one child died. The relapse rate was 64%. In comparison with an adult cohort, we found more ENT, heart, and digestive‐tract involvement, and fewer neurological manifestations. In children, the delay between asthma onset and diagnosis was shorter, and biopsies showed fewer features of vasculitis. Conclusion: This French cohort is the biggest pediatric EGPA series described to date, with a long follow‐up period. The findings confirm that pediatric EGPA has specific clinical, radiological, and histological characteristics that differ from adult EGPA. Development of systemic symptoms, and consequently diagnosis, occur with a shorter delay in children, mainly during the eosinophilic phase and leading to a specific presentation.